Turnaround strategy - The case of Malaysian Marble Sdn. Bhd. - Johari, Husna; Mohd Daud, Rusmala (Universiti Utara Malaysia, 1992)
Malaysian Marble Sdn. Bhd. (MMSB) incorporated in 17 June, 1981 was established to quarry and process marble from the limestone quarries of Pulau Pelangi. When MMSB started their commercial production in the mid of 1983, the positive revenues anticipated was never achieved. Instead the company experienced losses for that year and also for the subsequent years. By 1986, the company wans almost auctioned for a price of $5 million. Hence, Consultant Managers (CM), was brought in to help the ailing company in 1987. Generally, the purpose of the study is to identify the weaknesses of MMSB before turnaround and the evaluate the present stage of the company after CM came into the picture.